Stratigraphic Study for the Cretaceous-Tertiary period in Qasab-Jawan area in north weastern Iraq by using 2D seismic survey - Shehab, Marwa H.; Ali, Kamal K. (Iraqi Journal of Science, 2021)
A seismic study was conducted to re-interpret the Qasab and Jawan Oil fields in northwestern Iraq, south of the city of Mosul, by reprocessing many seismic sections of a number of field surveys by using the Petrel software. Two reflectors, represented by the Hartha formation, deposited during the Cretan age, and the Euphrates formation, formed during the Tertiary age, were delineated to stabilize the structural picture of these fields. The stratigraphic study showed that the Qasab and Jawan fields represent areas of hydrocarbon accumulation. Seismic attribute analysis showed low values of instantaneous frequency in the areas of hydrocarbon accumulation. Instantaneous phase was used to determine the limits of the sequence, the nature of sedimentation, and the type of vanishing, i.e. onlap vs. toplap. Low instantaneous amplitude values were recorded, indicating hydrocarbon reservoirs in the studied area. Various other seismic stratigraphic features were studied , including the distribution mound, flat spot, and channels in the two formations, but they were discontinuous because of the tectonic effects. These activities explain reasonably the distribution of hydrocarbons in the studied area.